Wija Kusuma Dance Accompaniment Music | Musik Iringan Tari Wija Kusuma - Putu Saldi (GHURNITA: Jurnal Seni Karawitan, 2023)
In socio-cultural life, especially on the islands of Bali and Indonesia in general, it will never be separated from the elements of percussion or musical art and also the art of movement or dance, these two elements cannot be separated from one another such as the concept of purusa and pradana. Likewise with the yadnya ceremony procession and the implementation of the event without being accompanied by gamelan and dance the nuances will feel much different. something that is lacking in this era of culture that used to have glory has been revived as a step for the development and preservation of a superior culture. In Bali there are many welcoming dances and other dances, this welcoming dance is used to welcome the arrival of invited guests and ceremonies either in the form of religious or artistic entertainment. Raising the title "wija kusuma" which is a welcoming dance art, from this work it is very important for the stylist to create a welcoming dance art, where the welcoming dance performance is a form of symbol as the opening of certain events or events, which are usually for religious events. The art of welcoming dance is very important to be performed at the beginning of the opening of a religious event and to welcome the invitees or invited guests so that they feel respected and entertained.